Accountability and objectivity: Humanitarian narratives at the intersection of evidence and localisation - Ellen Turner; Michelle Lokot; Isabelle L. Lange; Caitlin Wake; Bayard Roberts (Journal of International Humanitarian Action)
Abstract In the last decade, there has been a push for greater evidence-based practice within the humanitarian sector, alongside an increasing turn towards localising humanitarian assistance. Humanitarian actors and organisations have been increasing their production and use of evidence, while also being encouraged to reflect more critically on power hierarchies and decolonise humanitarian aid. This paper explores the intersection of these two narratives, examining how the use of evidence in humanitarian decision-making fits within a localisation agenda. Based on interviews with humanitarian health practitioners located globally, we examine how evidence is defined, and how it is used, including to inform both hierarchical and bottom-up approaches to decision-making. We find clear hierarchies about what counts as good evidence, with a weighting towards randomised-controlled trials, and that the perspectives of populations most affected by crises and the expertise of local actors were not routinely seen as central forms of evidence. Narratives about needing to build the capacity of local actors persist, alongside the notion of evidence as objective. We suggest that a disconnect exists between humanitarian discourses about evidence and localisation, arguing for the need to view evidence as political and influenced by researcher positionality This suggests that more consideration of locally-driven knowledge is needed and will strengthen humanitarian decision-making. We argue that a distinction between evidence and localisation does a disservice to both agendas and that finding synergies between these concepts would strengthen both.